Parody as film genre : "never give a saga an even break" - Gehring, Wes D. (Contributions to the study of popular culture ;, 1999)
An overview of the place of parody in film history. It defines the genre, differentiating it from satire, and demonstrates how a well-executed spoof provides an educational blueprint of its target genre. Films discussed include "Destry Rides Again" (1939) and "Scream" (1996)